PENGARUH SOSIALISASI, PEMAHAMAN PERPAJAKAN, DAN TARIF PAJAK PP NO. 23 TAHUN 2018 TERHADAP KEPATUHAN WAJIB PAJAK UMKM PADA KPP PRATAMA TIGARAKSA TAHUN 2023 - Wulandari, Winda; Lumbanbatu, Artabo Will More (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the influence of tax socialization, tax understanding, and the tax rate under Government Regulation No. 23 of 2018 on MSME taxpayer compliance at KPP Pratama Tigaraksa in 2023. The study is motivated by the persistently low tax compliance rate among MSME actors. A quantitative research method was employed using a survey approach, with data collected from 100 respondents and analyzed through multiple linear regression. The results show that tax socialization and tax understanding have a positive and significant effect on MSME taxpayer compliance, while the tax rate does not have a significant effect. Simultaneously, the three independent variables influence taxpayer compliance with a coefficient of determination of 76.7%. These findings highlight the importance of enhancing tax socialization and understanding to improve tax compliance in the MSME sector.